ChemInform Abstract: Application of Metal and Metal Oxide Nanoparticles @ MOFs. Issue 9 (February 2016) - Falcaro, Paolo; Ricco, Raffaele; Yazdi, Amirali; Imaz, Inhar; Furukawa, Shuhei; Maspoch, Daniel; Ameloot, Rob; Evans, Jack D.; Doonan, Christian J.
Abstract: Review: 201 refs.